Catheterization laboratory activity before and during COVID-19 spread: A comparative analysis in Piedmont, Italy, by the Italian Society of Interventional Cardiology (GISE). (15th January 2021) - Quadri, Giorgio; Rognoni, Andrea; Cerrato, Enrico; Baralis, Giorgio; Boccuzzi, Giacomo; Brscic, Elvis; Conrotto, Federico; De Benedictis, Michele; De Martino, Leonardo; Di Leo, Angelo; Ferrari, Fabio; Gagnor, Andrea; et al.
Abstract: Background: COronaVIrus Disease 19 (COVID-19) led to the reorganization of Cardiology Units in terms of working spaces and healthcare personnel. In this scenario, both outpatient visits and elective interventional cardiology procedures were suspended and/or postponed. We aimed to report the impact of COVID-19 on interventional coronary and structural procedures in Piedmont, Italy. Methods: The number of coronary angiographies (CAG), percutaneous coronary interventions (PCI), primary PCI (pPCI), transcatheter aortic valve replacements (TAVR) and Mitraclip performed in Piedmont between March 1st and April 20th, 2020 (CoV-time) were collected from each catheterization laboratory and compared to the number of procedures performed the year before in the same months (NoCoV-time). Results: Procedural data from 18 catheterization laboratories were collected. Both coronary (5498 versus 2888: difference: −47.5%; mean 305.4 VS 160.4; p = 0.002) and structural (84 versus 17: difference: −79.8%; mean 4.7 Vs 0.9; p < 0.001) procedures decreased during CoV-time compared to NoCoV-time. In particular, coronary angiographies (1782 versus 3460), PCI (1074 versus 1983), p PCI (271 versus 410), TAVR (11 versus 72) and Mitraclip (6 versus 12) showed a reduction of 48.5%, 45.7%, 33.7%, 84.7% and 50.0%, respectively (all p for comparison <0.05). Conclusions: Compared to the same time-period in 2019, both coronary and structural interventional procedures during COVID-19 epidemic suffered a dramatic decrease in Piedmont, Italy. Organizational change and structured clinical pathways should be created, together with awareness campaigns. Highlights: COronaVIrus Disease 19 (COVID-19) led to the reorganization of Cardiology Units Interventional procedures during COVID-19 suffered a dramatic decrease in Piedmont Structured clinical pathways should be created, together with awareness campaigns.